1973
DOI: 10.1002/jsfa.2740241205
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of aroma and flavour characteristics of mango (Mangifera indica L.) to fatty acid composition

Abstract: Glyceride content and fatty acid composition of pulp from five commercial varieties of table-ripe mangoes having wide differences in aroma and flavour were studied. In addition, the Alphonso mango was examined at various stages of ripening at two different temperatures. Although the same type of fatty acids were present in all varieties of ripe mango there were differences in quantitative distribution. During the ripening of Alphonso mango at ambient temperature (25 to 30 "C), there was an increase in the glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 3 publications
3
11
0
Order By: Relevance
“…The pulps from four market types of mangoes examined contained 0.2-0.3 wt % (wet basis} total lipids including O-acy] lipids, free fatty acids, sterols, pigments and other lipids. The contents of the total lipids were lower as reported previously with mangoes of India growth (33)(34)(35) than those of common edible oil seeds. The amount of pulp total lipids in mango from the Philippines was ca.…”
Section: Resultssupporting
confidence: 45%
“…The pulps from four market types of mangoes examined contained 0.2-0.3 wt % (wet basis} total lipids including O-acy] lipids, free fatty acids, sterols, pigments and other lipids. The contents of the total lipids were lower as reported previously with mangoes of India growth (33)(34)(35) than those of common edible oil seeds. The amount of pulp total lipids in mango from the Philippines was ca.…”
Section: Resultssupporting
confidence: 45%
“…However, they could not derive any correlation between the aroma and lipid composition. With mangoes, on the other hand, a relationship between the aroma and flavor characteristic with fatty acid composition of the pulp has been ascertained (6,7). It was observed that the ripening of Alphonso mango was associated with concurrent changes in glyceride content and fatty acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Except palmitic, palmitoelic and linolenic acids, all other major fatty acids increased during ripening (Lalel et al 2004b). The fatty acid composition in fruit pulp has direct relationship with the aroma and flavour of mango fruit (Bandyopadhyay & Gholap 1973b). A relation between aroma and flavour of the fruit and the ratio of palmitic acid to palmitoleic has been proposed.…”
Section: Lipids and Phenolsmentioning
confidence: 99%
“…A relation between aroma and flavour of the fruit and the ratio of palmitic acid to palmitoleic has been proposed. If the ratio was less than 1, the fruit had a strong aroma and if more than 1, the fruit had a mild aroma (Bandyopadhyay & Gholap 1973b). An unusual fatty acid, named mangiferic acid (cis-9, cis-15-octadecadienoic acid), has been identified in the pulp of mango fruit which constitutes 5.4% of total acyl groups in the pulp lipids; whereas a common octadecadienoic acid, linoleic acid, is a minor component (1.1%) in the same lipids (Shibahara et al 1993).…”
Section: Lipids and Phenolsmentioning
confidence: 99%